1985
DOI: 10.1021/jm00150a017
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting binding of trans-N-[2-(methylamino)cyclohexyl]benzamides at the primary morphine receptor

Abstract: In this paper, we describe the synthesis of a series of trans-N-[2-(methylamino)cyclohexyl]benzamides possessing morphine-like pharmacological properties. The affinity of the compounds for the agonist and antagonist states of the mu opioid receptor has been established by means of an in vitro binding assay. We have investigated the geometry and electronic structure of the molecules using molecular mechanics and an ab initio SCF-MO procedure with FSGO basis sets. Comparison to naloxone reveals properties of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 4 publications
(10 reference statements)
1
66
0
Order By: Relevance
“…Of particular relevance to this point are (1) reports of high lipid/water partition coefficients of drugs with very similar structures to U-50,488 (see Cheney et al, 1985) and (2) the rapid time to peak effect and subsequent rapid redistribution to the systemic circulation of the selective K-ligand PD1 17302 administered i.c.v. (Leighton et al, 1988 (Czlonskowski et al, 1983;Slater & Patel, 1983) but not by all (Morris & Herz, 1987) studies on the regional localisation of spinal K-opioid binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance to this point are (1) reports of high lipid/water partition coefficients of drugs with very similar structures to U-50,488 (see Cheney et al, 1985) and (2) the rapid time to peak effect and subsequent rapid redistribution to the systemic circulation of the selective K-ligand PD1 17302 administered i.c.v. (Leighton et al, 1988 (Czlonskowski et al, 1983;Slater & Patel, 1983) but not by all (Morris & Herz, 1987) studies on the regional localisation of spinal K-opioid binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of U-47700 and other derivatives was disclosed by the Upjohn Company in the 1970s [7] followed by the recognition that U-47700 showed increased analgesic properties and morphine-like behavioural features in mice compared to morphine itself. [8,9] The presence of two chiral centres gives rise to a cis-and trans-racemic mixture with the trans-form being advertised for sale. Binding studies also revealed that U-47700 displayed an appreciable selectivity for the µ-opioid receptor over the κ−opioid receptor.…”
Section: Introductionmentioning
confidence: 99%
“…developed by Upjohn in the 1970s, which has never been studied in humans and its not approved for medical use. Very little, if any, information is available from scientific literature [10]. The substance is openly sold on the internet.…”
Section: Sample Preparation and Extractionmentioning
confidence: 99%